A Hybrid Science Learning Model Integrating Local Wisdom and Digital Technology to Enhance Scientific Literacy and Ecological Character of Elementary School Students (SDG 4) - Tuti Liana; Afkar; Faizah M. Nur; Fatemah Rosma; Maizura Fauzie (Postgraduate, University of Mataram, 2026)
This study aimed to develop and implement a hybrid biology learning model integrating local wisdom and digital technology to improve scientific literacy and strengthen the ecological character of elementary school students. A Design-Based Research (DBR) approach was employed, involving fifth-grade students as research subjects. Data were collected through observations, interviews, scientific literacy tests, ecological character questionnaires, and documentation. Quantitative data were analyzed using N-Gain and paired sample t-tests, while qualitative data were analyzed through data reduction, data display, and conclusion drawing. The results showed a significant improvement in students’ scientific literacy, with average scores increasing from 55.4 to 81.7 and an N-Gain value of 0.60 (moderate category). Students’ ecological character also improved from 68.35 (fair) to 86.94 (very good). Teachers’ and students’ responses indicated that the model was practical, engaging, and easy to implement, while expert validation confirmed its validity and feasibility. Overall, the findings indicate that the proposed hybrid learning model offers an effective and innovative approach for enhancing both cognitive and affective learning outcomes in elementary science education.